Comparison between isometric and plyometric warming exercises on standing vertical jump performance - Beliaeff, S.; Legreneur, P.; Creveaux, T.; Haguenauer, M.; Monteil, K. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Plyometric exercise is often used to improve power and vertical jump performance. Some researches suggested that plyometric performance was enhanced after having performed practice jumps (Young and Behm, 2003). On the other hand, some studies proposed that a warming up protocol including a strength-training program could be used for short-term improvements on vertical jumping performance (Gourgoulis et al, 2003). To our knowledge, there is no investigation aimed at comparing the influence of these two warming up programs on vertical jump performance. Therefore, the purpose of this study was to analyse the effect of isometric and plyometric warming exercises on standing vertical jump performance and to determine if there was an optimal time for performing plyometrics after these two training sets. Methods Nine national male athletes volunteered to participate in the present study. The experiment consisted of two laboratory sessions separated by one day rest. Subjects executed in a random order isometric and plyometric trainings. Each session was organised as follows: test1-isometric or plyometric training-test2-test3-test4-test5. Each test was composed of two maximal countermovement jumps (CMJ) with a rest interval of 30 seconds. Isometric training was constituted of 5 isometric maximal voluntary contractions (MVC) of 3 seconds duration performed on a guided barbell in a half-squatting position. Between each trial, 1minute rest was retained. Plyometric training consisted in 20 maximal bounce drop jumps carried out successively from a height of 45 cm. The resting period between test1 and training session was 2 minutes. Test2, test3, test4 and test5 were achieved with an interval of 1min, 4min30, 8min and 11min30 following the training session end respectively. Each subject performed these two CMJ on a force plate (500Hz). Jump height (Hmax) was calculated from the flying time. Explosive force was assessed by concentric time, peak concentric ground reaction force (GRF), time to attain peak concentric GRF, rate of force development and peak concentric power. Repeated measures ANOVA were used for statistical analysis. Student test was completed to identify significant effect between temporal and training conditions. Results With regard to jump height (Hmax), there was no significant difference between the two control test1 prior isometric and plyometric warm up exercises. Concerning plyometric condition, CMJ performance was significantly increased until test3 (+8.10%). In spite of a significant drop between test3 and test5, vertical jump performance was still significantly greater in test5 than in test1. Peak concentric GRF, peak concentric power, rate of force development were significantly enhanced after plyometric warm up of 10.46%, 7.19%, 18.51% respectively while concentric time was significantly lower (-6.34%) and no significant result was observed for time to attain peak concentric GRF. Considering isometric condition, there was no effect on jump performance and explosive force. However, a non significant trend toward improvement in jump height (+4.67%) seemed to be present in test2. Significant differences were found between isometric and plyometric sessions at test3, test4 and test5 (Fig.1). For test2, test3, test4 and test5, plyometric warm up yielded significantly better score than isometric one for peak concentric GRF (+15.89%), peak concentric power (+10.99%) and rate of force development (+24.36%). Concentric time was significantly lower (-9.58%) following the plyometric session than isometric one. There was no significant difference for time to attain peak concentric GRF between two training conditions. Discussion/Conclusion Isometric warm up did not appear to enhance jumping performance significantly whereas plyometric one had a positive effect on explosive force and jumping performance. To optimise jump performance, it seemed that athletes should perform jump 4min30 following the plyometric session and significant effect was still present at 11min30. A warm up protocol including bounce drop jumps can be practised to improve vertical jumping performance and explosivity not only for short-term positive effect but also for middle term changes.